ASIMILASI PERUBAHAN BUNYI NASAL DAN NON-NASAL PADA BAHASA ARAB - Lathifatussa’diyyah, Siti; Umam, Khaerul (Universitas Sebelas Maret, 2022)
This study describes the assimilation of nasal and nonnasal sound changes in Arabic. The sound change is the process of changing the sound caused by the presence of other sounds that are close to each other. This study aims to find phonological pattern phenomena that occur in Arabic, based on distinctive features studies. This research is a qualitative descriptive study. While the data collection method in this study is the observation method and uses note-taking techniques. The research data source is in the form of Arabic data which is contained in the Holy Qur'an. Assimilation in nasal and nonasal sounds in Arabic is known as idgham. The results showed that there are two types of assimilation of nasal sounds in Arabic, namely partial assimilation (idgham bigunnah) and complete assimilation (idgham bilagunnah). Meanwhile, the assimilation of nonnasal sounds in Arabic occurs in the reading of idgham mutaqaribain and idgham mutajanisain